2000
DOI: 10.1097/00007632-200007150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Longer Than 10-Year Follow-Up of Patients With Rheumatoid Arthritis Treated by Occipitocervical Fusion

Abstract: Occipitocervical fusion for patients with rheumatoid arthritis is useful for decreasing nuchal pain, reducing myelopathy, and improving prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 21 publications
1
40
1
5
Order By: Relevance
“…The incidence of subaxial subluxation was low, corresponding to the 17% of the treated patients. If we consider, however, that such occurrence was reported just in the group of patients affected by rheumatoid arthritis, this value raises to 30% and it is in concordance with the literature [5,8]. The absence of this complication in tumoral pathology is probably related to the limited survival period of these patients which generally does not allow for a long followup.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The incidence of subaxial subluxation was low, corresponding to the 17% of the treated patients. If we consider, however, that such occurrence was reported just in the group of patients affected by rheumatoid arthritis, this value raises to 30% and it is in concordance with the literature [5,8]. The absence of this complication in tumoral pathology is probably related to the limited survival period of these patients which generally does not allow for a long followup.…”
Section: Discussionsupporting
confidence: 83%
“…Several reports exist about the significance of rheumatoid arthritis in the pathogenesis of atloaxial and subaxial instability. Matsunaga et al [8] reported an incidence of subluxation of 34% on a series of patients affected by rheumatoid arthritis in advanced disease. Kraus et al [5] reported an incidence of 36% in a similar series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that, in operated patients, additional long fusion surgery have been caused by newly developed instability and decompensation of the adjacent segments after the atlanto-axial or occipito-cervical fusions [9][10][11][12][13][14]. Newly developed subluxation below a fused segment may occur in 20-36 % of RA patients after cervical fusion [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Subaxiale Anschlussinstabilitäten sind bei der RA ein häufiges Problem und treten deshalb zunehmend in den Blickpunkt des Interesses [19,30,[32][33][34] Es sollte deshalb bereits in der primären OP-Planung gezielt nach einer segmentalen subaxialen Problematik gesucht werden (z. B. segmentale Gleitbewegung, Malalignment in Lordose oder inflammatorische Prozesse).…”
Section: N Atlantoaxiale Fusionunclassified